Wordwall-Based Digital Media to Stimulate Students in Learning English Vocabulary - Komang Santi Widi Rahayu; I G A Lokita Purnamika Utami (Universitas Pendidikan Ganesha, 2023)
In the current digital era, conventional learning media are often considered less attractive for students, especially amidst the dominance of technology in everyday life. The use of digital media such as Wordwall, an interactive learning platform that offers various educational games, is believed to increase students' interest and motivation in learning. Based on previous findings, this research focuses on creating Wordwall media to teach English vocabulary to 5th grade elementary school students. Students have never used learning media designed for vocabulary learning. This research uses the Design and Development (DnD) research paradigm to construct learning media in the form of Wordwalls. The DnD research model consists of three main stages: design, development, and assessment. Researcher notes, validation sheets, expert assessments, and user questionnaires are the instruments used in this research. The subjects of this research were 5th grade elementary school students. The main results of this research show significant results, this shows that the media developed is very good and suitable for use. This research aims to identify how using Wordwall can help students master new vocabulary, strengthen their memory, and increase their involvement in the learning process. The implications of this research indicate that the use of Wordwall-based digital media has significant potential to stimulate students' interest and motivation in learning English vocabulary. By integrating Wordwall in learning activities, teachers can create a more interactive and interesting learning environment, thereby increasing student engagement and speeding up the process of understanding new vocabulary.